Incidence, Outcome, and Predictors of Intracranial Hemorrhage in Adult Patients on Extracorporeal Membrane Oxygenation: A Systematic and Narrative Review - Fletcher-Sandersjöö, Alexander; Thelin, Eric Peter; Bartek, Jiri; Broman, Mikael; Sallisalmi, Marko; Elmi-Terander, Adrian; Bellander, Bo-Michael (Frontiers in Neurology, 2018)
Background: Intracranial hemorrhage (ICH) is a common complication in adults treated with extracorporeal membrane oxygenation (ECMO). Objectives: The aim of this study was to conduct a systematic review of the literature on the incidence, outcome and predictors of ECMO-associated ICH in adult patients, supplemented by a narrative review of its pathophysiology, management and future perspectives. Methods: MEDLINE, EMBASE, Cochrane Database of Systematic Reviews and www.clinicaltrials.gov were systematically searched. Studies that reported incidence, outcome or predictors of ECMO-associated ICH in adults (≥18 years) were eligible for inclusion. Results: 25 articles were included in the systematic review. The incidence of ECMO-associated ICH varied between 1.8 - 21 %. Mortality rates in ICH-cohorts varied between 32 - 100 %, with a relative risk of mortality of 1.27 - 4.43 compared to non-ICH cohorts. An increased risk of ICH was associated with ECMO-duration, antithrombotic therapy, altered intrinsic coagulation, renal failure, need of blood products, rapid hypercapnia at ECMO initiation and even pre-ECMO morbidity. Conclusions: ICH is a common complication in adults treated with ECMO and associated with increased mortality. Treating an ICH during ECMO represents a balance between pro- and anticoagulatory demands. Neurosurgical treatment is associated with severe morbidity, but has been successful in selected cases. Future studies should aim at investigating the validity and feasibility of non-invasive monitoring in early detection of ECMO-associated ICH.